EFFECT OF FAITH-BASED INTERVENTION ON DIETARY BEHAVIOUR CHANGE - Suriani Ismail; Khadijah Shamsuddin; Khalib Abdul Latiff; Hazizi Abu Saad; Latifah Abd Majid; Fadlan Mohd.Othman (PERINTIS eJournal, 2021)
Many religious teachings are in line with health objectives, thus providing great opportunities for faith-based health interventions. In this intervention, Islamic teachings were used as the mediator to change dietary behavior to control weight. The promoted dietary practices were voluntary fasting and food portion control. A quasi experiment was carried out to test the effectiveness of this faith based dietary intervention. Two dietary interventions were developed. One was the faith-based dietary intervention and the other was a basic dietary intervention. The intervention packages developed were then validated. Two groups of Muslim women were recruited for the study. The faith-based intervention group received an Islamic intervention package while the basic intervention group received a basic intervention package (i.e. without the faith components). Their baseline dietary practices were assessed prior to intervention and reassessed at 3 months post ‘active intervention phase’. After 3 months of ‘active intervention phase’, the number of respondents who practiced voluntary fasting has increased significantly in the faith-based intervention group, while it was slightly reduced in the basic intervention group. As for food portion control practices, the number of respondents who practiced such control were significantly increased in both groups, however